Protagonismo em uma cultura de quadrinhos? : as facetas de Jane Foster e a representação feminina para além das páginas - Lettícia Gabriella Carvalho de Oliveira (2022)
Even if they suppose a rupture with reality due to their fictional character, comics carry forms of representation of the medium, and may indicate power relations and perceptions about gender and social roles. Considering culture as an integral way of life, where the material and the cultural cannot be dissociated, this research aims to analyze the dominant, residual, and emerging relations in comic book culture, since it can engender disputes for hegemony by organizing itself as an industry and activating reading repertoires, giving rise to a wide textual network. Having as empirical object the character Jane Foster, from Marvel Comics, the proposal discusses the tensions provoked by her throughout her trajectory, once she dissociated herself from the stigma of being a damsel in distress and became the bearer of the titles of Mighty Thor and Valkyrie, taking the lead in the plots. Having Cultural Studies as the main theoretical basis and the proposal of the structure of feeling discussed by Raymond Williams, we will observe aspects that permeate the female protagonism in the superhero genre, alluding to the female presence inside and outside the pages and how this contributes to delineate the way women were and still are seen and represented culturally.